Evaluating the effectiveness of electrical remodeling in patients after anterior cruciate ligament - Ячнік [Sergey Yachnik], Сергій Петрович; Кравчук [Ludmila Kravchuk], Людмила Дмитрівна; Ніканоров [Akeksey Nikanorov], Олексій Константинович (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Еlectromyostimulation effect on motor function of the quadriceps femoris muscle in the process of physical rehabilitation of patients after arthroscopic anterior cruciate ligament reconstruction were considered in the article. The analysis and synthesis of special scientific and methodological literature on the most typical violations of motor function in patients in the postoperative period were studied by electromyography parameters of bioelectrical activity of the quadriceps femoris. In pedagogical experiment involved 20 patients aged 25–35 years. Found that the use of electromyostimulation in combination with physiotherapy can improve the effectiveness of rehabilitation. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->